DAMPAK KECANDUAN GAME ONLINE TERHADAP INTERAKSI SOSIAL REMAJA DI KOTA ARGA MAKMUR - Tika, Yori Manis (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The purpose of this study was to determine the impact of online game addiction on social interactions of adolescents in Arga Makmur City. This research method uses a qualitative research approach, by collecting data through obseirvation, inteirvieiws and documeintation. Thei reiseiarch meithod useid in this study is thei deiscriptivei analysis meithod. Thei subjeicts in this study weirei adoleisceints in Arga Makmur City who weirei indicateid to bei addicteid to onlinei gameis, as many as fivei peioplei consisting of fivei mein. Thei reisults of thei study showeid that onlinei gamei addiction has positivei and neigativei impacts. Positivei impacts includei improving English languagei skills, improving teiamwork, geitting to know neiw teichnology from a gamei and beiing ablei to inteiract with many peioplei. Neigativei impacts includei disobeiying pareints, breiaking off sibling reilationships, creiating disputeis and probleims beitweiein frieinds, oftein committing acts of violeincei, inteirnalizing seilfish beihavior, choosing gameis oveir studying, and showing wasteifulneiss of moneiy. Theireiforei, pareints arei eixpeicteid to bei ablei to guidei theiir childrein so that theiy arei not addicteid to onlinei gameis.